Perceptions of Therapeutic Intervention in Suicide Crisis Counseling in Experienced Korean Counselors: A Concept Mapping Study - Park, AeShil; Kim, Dongil; Shin, HyeYun Gladys (Frontiers in Psychiatry, 2022)
Within Organization for Economic Cooperation and Development (OECD) nations, South Korea has the highest suicide rate for which immediate prevention measures are sought including effective therapeutic counseling interventions. As such, the present study explored and examined experienced South Korean counselors’ perception of therapeutic interventions for the prevention or delaying completed suicide, using concept mapping methodology. The semi-structured interviews were provided to 15 study participants of experienced counselors having a minimum of 5 years of professional counseling career and at least 10 suicide crisis counseling sessions. A total of 77 statements were extracted with 8 major clusters: “Securing Safety,” “Active Advocacy for Client,” “Coping Skills Training,” “Conceptualization of Suicide Crisis,” “Emotional Identification and Validation,” “Empowerment,” “Counselor Self-disclosure,” “Counselor Self-awareness and Regulation.” From the results, the present study described unique findings in Korean counselors’ perceptions of suicide crisis therapeutic intervention. Study limitations and future implications are further discussed.